2015
DOI: 10.1093/cid/civ256
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and TransientHelicobacter pyloriInfections in Early Childhood

Abstract: These results indicate that persistent H. pylori infections acquired early in life are associated with specific host and/or strain profiles possibly associated with future disease occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 33 publications
2
56
3
4
Order By: Relevance
“…In several articles, transient H. pylori infections were reported in childhood. O'Ryan et al . evaluated factors associated with persistent or transient infection among 332 Chilean asymptomatic children.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…In several articles, transient H. pylori infections were reported in childhood. O'Ryan et al . evaluated factors associated with persistent or transient infection among 332 Chilean asymptomatic children.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…Overall, sensitivity of these tests seems to be lower than ELISA , although a few studies suggested high specificity, of >90% when compared to invasive tests . Our research group, along with many others , have based our studies in children on ELISA results, and thus, the relatively high rtPCR‐positive/ELISA‐negative samples detected in samples from our previous study (1/3 of samples tested) required clarification. Importantly, it is conceivable that some children had a persistent infection that was not detected by ELISA.…”
Section: Discussionmentioning
confidence: 85%
“…Cohort studies using direct detecting of H. pylori infection, by stool antigen or UBT, at ≥3 time points in apparently healthy children are displayed in Table . The prevalence of H. pylori infection in cohorts including children <5 years of age was 20% in Portugal, 27% in Brazil, 33% in Israel, 34% and 41% in Chile and 50% in Peru . For children >5 years of age, infection rates were 38% in Mexico and 42% in Portugal .…”
Section: Resultsmentioning
confidence: 96%
“…For high‐income countries, 8%‐20% (median: 20%) of all children had long‐term infection. A persistent infection most probably represents a chronic infection, although reinfections cannot be excluded . For cross‐sectional studies, the likelihood that one positive sample indicting an active infection (based on UBT or stool antigen) reflects a persistent infection would therefore be around 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation